2011
DOI: 10.1186/1752-1505-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Six rapid assessments of alcohol and other substance use in populations displaced by conflict

Abstract: BackgroundSubstance use among populations displaced by conflict is a neglected area of public health. Alcohol, khat, benzodiazepine, opiate, and other substance use have been documented among a range of displaced populations, with wide-reaching health and social impacts. Changing agendas in humanitarian response-including increased prominence of mental health and chronic illness-have so far failed to be translated into meaningful interventions for substance use.MethodsStudies were conducted from 2006 to 2008 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 65 publications
5
159
0
Order By: Relevance
“…In a review of 10 studies on substance abuse, Ezard has suggested that substance use (e.g., alcohol, opiates or minor tranquilizers) is common in some displaced settings (14).…”
Section: Substance Use and Displaced Population Groupsmentioning
confidence: 99%
“…In a review of 10 studies on substance abuse, Ezard has suggested that substance use (e.g., alcohol, opiates or minor tranquilizers) is common in some displaced settings (14).…”
Section: Substance Use and Displaced Population Groupsmentioning
confidence: 99%
“…For example, an epidemiological study in conflict-affected Timor-Leste found high rates of psychotic-like symptoms (predicted by traumatic events) which were strongly associated with disability (Silove et al, 2008;Soosay et al, 2012). Similarly, rapid assessments in a variety of refugee populations have identified alcohol and substance use disorders as an important mental health problems (Ezard et al, 2011). Very little research has focused on dissociative disorders in conflict-affected settings, even though they have been shown to be associated with exposure to traumatic events and may be a common idiom of distress in conflict-affected populations (van Duijl et al, 2010).…”
mentioning
confidence: 99%
“…This study also contributes to the evidence base necessary to establish priorities among agencies working with conflict-affected populations to rebuild substance abuse treatment systems and related healthcare infrastructures. Strengthening substance abuse treatment systems among conflict-affected populations will be critical to implementing more comprehensive treatment services for substance use disorders including cognitive, behavioral and drug therapies for substance dependence and identification and treatment of a variety of physical and psychiatric disorders that are often comorbid with substance use disorders (Ezard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse health care services are disrupted through damage to water supplies, electricity, and sewage disposal necessary for health services to operate, coupled with injury, death and disappearance of health care workers (Ezard et al, 2011;Hansch and Burkholder, 1996;Perrin, 1996). Agricultural systems are disrupted resulting in food rations, an important ingredient that has been implicated in facilitating home-brewed alcohol production in conflict-affected populations (Adelekan, 2006;Ezard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%